Long-Term Sleep Deprivation-Induced Myocardial Remodeling and Mitochondrial Dysfunction in Mice Were Attenuated by Lipoic Acid and N-Acetylcysteine - Fei Song; Jiale Lin; Houjian Zhang; Yuli Guo; Yijie Mao; Zuguo Liu; Gang Li; Yan Wang (MDPI AG, 2022)
The impact of long-term sleep deprivation on the heart and its underlying mechanisms are poorly understood. The present study aimed to investigate the impact of chronic sleep deprivation (CSD) on the heart and mitochondrial function and explore an effective drug for treating CSD-induced heart dysfunction. We used a modified method to induce CSD in mice; lipoic acid (LA) and N-acetylcysteine (NAC) were used to treat CSD mice. Echocardiography, hematoxylin-eosin (H&E) staining, Sirius red staining, and immunohistochemistry were used to determine heart function and cardiac fibrosis. The serum levels of brain natriuretic peptide (BNP), superoxide Dismutase (SOD), micro malondialdehyde (MDA), and glutathione (GSH) were measured to determine cardiovascular and oxidative stress-related damage. Transmission electron microscopy was used to investigate mitochondrial damage. RNA-seq and Western blotting were used to explore related pathways. We found that the left ventricular ejection fraction (LVEF) and fraction shortening (LVFS) values were significantly decreased and myocardial hypertrophy was induced, accompanied by damaged mitochondria, elevated reactive oxygen species (ROS), and reduced SOD levels. RNA-sequence analysis of the heart tissue showed that various differentially expressed genes in the metabolic pathway were enriched. Sirtuin 1 (Sirt1) and Glutathione S-transferase A3 (Gsta3) may be responsible for CSD-induced heart and mitochondrial dysfunction. Pharmacological inhibition of ROS by treating CSD mice with LA and NAC effectively reduced heart damage and mitochondrial dysfunction by regulating Sirt1 and Gsta3 expression. Our data contribute to understanding the pathways of CSD-induced heart dysfunction, and pharmacological targeting to ROS may represent a strategy to prevent CSD-induced heart damage.